Determinación de la contaminación del agua por sólidos suspendidos, generado por el uso de alimento balanceado en la piscicultura - García Paredes, Franco Luis (2014)
with 09 fish farms authorized by the corresponding entity to produce a total of between 2 to 50 metric tons per year (smaller scale), which make use of the balanced food for the feeding of the fish in the entire production process, food that currently found in the local market in its different presentations. Through this research work was able to ascertain the degree concentration of total suspended solids in the water that is used in the fish raising, solids to be increased by the use of balanced food in the productiva process; todo this from the total of fish farms authorized leve! of smaller scale is proceeded to monitor the resource water by placing two monitoring stations for each fish-breeding farm evaluated (four farms in total), one of the income of the water to the fishbreeding farm and another in the center of the pond that is in production; the frequency of monitoring were with thirty days intervals by a time of four consecutiva months. For the fish farms assessed selection it was taken into account criteria such as location, entry and exit of independent water, production leve!, the activity authorization, production start, and use the 1 00% balanced food in the productiva process. The results obtained tells us that food supply extruzado balanced in the power of the activity of raising fish in ponds controlled is increasing, in the present account with 09 fish farms authorized by the corresponding entity to produce a total of between 2 to 50 metric tons per year (smaller scale), which make use of the balahced food for the fish feeding in the entire production process, food that currently found in the local market in its different presentations. Through this research work was able to ascertain the degree concentration of total suspended solids in the water that is used in the raising of fish, solids to be increased by the use of balanced food in the productiva process; to do this from the total of fish farms authorized level·of smaller scale· is proceeded to monitor the resource water by placing two monitoring stations for each fishbreeding farm evaluated (Four farms in total), one of the income of the water to the fishbreeding farm and another in the center of the pond that is in production; the frequency of monitoring were with thirty days intervals by a time of four consecutiva montlls. For the. selectio.n of fish fariXIS assessed it was. taken into. · account criteria such as location, entry and exit of independent water, production level, authorization of the activity, start of production, and use the 100% balanced food in the productiva process. The results obtained tells us that food supply extruzado balanced in the hydro biological species diet of fish farms assessed increases the solids in suspension in 54.49 ppm to 202.38 ppm what percentage represents a 371 %. The average value equivalent to 202.38 does not exceed the Environmental Quality Standards for Water Conservation of jungle that is 400 ppm, established by the environment Ministry. The presence of suspended solids in the ponds supply product of balanced food leads us to establish possible negative environmental